Exploitation of cost-effective renewable heterogeneous base catalyst from banana (Musa paradisiaca) peel for effective methyl ester production from soybean oil - Nurul Aina Nasriqah, Ma’arof; Noor, Hindryawati; Siti Norhafza, Mohd Khazaai; Bhuyar, Prakash; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam (Springer Berlin Heidelberg, 2021)
Biodiesel is one of the biofuel alternatives obtained from vegetable oils and animal fats, currently being used globally to lessen environmental pollutions. In this research investigation, waste banana peels impregnated with calcium oxide (CaO) were utilized as a catalyst in the transesterifcation reaction of soybean oil with methanol. The waste of banana peels was calcined at 700 °C for 4 h and then added with CaO, calcined at 900 °C for 3 h with diferent concentrations. The results obtained showed that CaO is successfully impregnated based on the SEM–EDX, the surface area of CaO-CBP was smoother than CaO, the BET results revealed that with CaO-CBP the surface area was increased which was exhibited a porous and rough shape on the calcined banana peel (CBP) to give a high yield. Methyl esters (FAME) are produced at the highest conversion of 76.87 wt. % under 7 wt.% of catalyst amounts, 9:1 of molar ratio of methanol to oil and 2 h reaction time, as optimum conditions. The CaO impregnated with CBP (30% CaO-CBP) was used as a potential catalyst for heterogeneous bases that can facilitate transesterifcation reaction efciently due to its high catalytic activity